Pajak Penghasilan di Indonesia : Peraturan dan Perhitungan - Sagita Nurul Adzani; Ola Maria; Rudi Sanjaya; Komaruddin Komaruddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines Income Tax provisions under the latest tax regulations in Indonesia, explains the procedures and mechanisms for calculating Income Tax based on the Law on Harmonization of Tax Regulations (HPP Law), and evaluates the contribution of Income Tax to state revenue and equitable income distribution. This research applies library research with a qualitative descriptive approach. The data were collected from relevant sources, including laws and regulations, academic books, scientific articles, research journals, and official government publications related to Income Tax policy in Indonesia. The data were analyzed systematically to identify regulatory developments, tax calculation mechanisms, and the implications of tax policy for national state revenue and fiscal justice. The findings show that the HPP Law establishes five progressive tariff layers for Individual Taxpayers, with a maximum rate of 35% imposed on taxable income exceeding IDR 5 billion per year. This provision reflects the principles of ability to pay and vertical equity in Indonesia’s tax system. Furthermore, the Corporate Income Tax rate of 22%, along with various rate-reduction incentives for eligible taxpayers, can enhance business competitiveness and reduce tax burdens. Tax administration modernization through e-Filing, e-Billing, e-Bupot, and Coretax also improves service efficiency and strengthens taxpayer compliance more effectively.